Pemberdayaan Masyarakat melalui Pelatihan Produksi Nugget Ayam dan Jantung Pisang Kepok sebagai Inovasi Pangan Lokal untuk Mendukung Peningkatan Produksi ASI - Sri Heryani; Yudita Ingga Hindiarti; Kurniati Devi Purnamasari; Anisa Puspitasari (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Breast milk production plays a crucial role in supporting infant growth and immunity. One of the efforts to improve breast milk production is by optimizing the nutritional intake of breastfeeding mothers through the utilization of local food sources. Kepok banana heart (Musa paradisiaca) contains essential nutrients and natural lactagogue compounds that have the potential to stimulate prolactin and oxytocin hormones. This community service program introduces the innovation of chicken nuggets combined with kepok banana heart as an alternative nutritious local food product for breastfeeding mothers. Objective: The purpose of this community service was to empower breastfeeding mothers and health cadres through training on processing kepok banana heart into an innovative food product and to improve their knowledge, skills, and attitudes regarding local food utilization to support breast milk production. Method: This public service activity was conducted through several stages, including initial surveys, socialization, nutrition education, demonstration of processing techniques, hands-on practice, and evaluation. A total of 30 participants consisting of breastfeeding mothers and cadres took part in the program. Evaluation was carried out using pre-test and post-test assessments to measure changes in knowledge, skills, and attitudes. Result: The training resulted in a significant improvement in participants’ abilities. Knowledge increased by 41.25% (p < 0.001), skills increased by 26.06% (p < 0.01), and attitudes increased by 13.06% (p = 0.018). Participants were able to independently process kepok banana heart into chicken nugget products and demonstrated positive interest in adopting local food innovations. The program also initiated the formation of a nutrition education group and prepared several academic outputs such as modules, HKI drafts, and documentation. Conclusion: The community empowerment program effectively enhanced participants’ knowledge, skills, and attitudes in utilizing local food ingredients, particularly kepok banana heart, as a nutritious innovation to support breast milk production. The activity shows strong potential for sustainability and can be replicated in other communities to promote food-based interventions for maternal and child health.